THEORETICAL VIEWS ON CONCEPTS OF ENTREPRENEURSHIP - Shadieva G.M.; Khusinova Shoira Akbarovna (Journal of new century innovations, 2023)
Abstract: This article is devoted to the consideration of the issues related to the disclosure of the social and economic concept of “family economy”, its development and conceptual ways to raise the welfare.